Irreversible calendar aging and quantification of the reversible capacity loss caused by anode overhang. (August 2018) - Lewerenz, Meinert; Fuchs, Georg; Becker, Lisa; Sauer, Dirk Uwe
Graphical abstract: Highlights: Anode overhang can lead to increase or decrease of extractable capacity. Quantification of the influence of anode overhang using only four parameters. Increase of homogeneity of lithium distribution during calendaric aging. Homogeneity can lead either to increase or to decrease of extractable capacity. Irreversible calendaric aging is a function of cathode potential. Abstract: Calendar aging tests are presented quantifying the reversible capacity loss caused by lithium migration from the active part to the overhang of the anode. Based on these tests, capacity loss at five different SOCs with respect to the anode is evaluated. The remaining capacity shows a non-linear part in the beginning representing the reversible capacity loss caused by the overhang. The subsequent linear part ending after 100–200 days corresponds to the irreversible capacity loss. By extrapolating the linear part to t = 0, the lithium lost to the overhang is measureable for each storage condition. This approach matches well to theoretical values calculated using a simple equation. In later stages of the capacity loss curve, another superposed effect can be observed that decreases capacity fade. The reason is found in an increasing homogeneity of lithium distribution that correlates to the peak height of differential voltage characteristics. In this publication an increasing homogeneity is associated with a higher extractable capacity and vice versa. An especially high increase of homogeneity is observable when a high voltage difference coincides with pressure change due to lithium insertion. Finally, the temperature dependency of the lateral lithium flow is shown for three temperatures at a fixed storage position.